Peluang Social Commerce Melalui Akuisisi Tokopedia Oleh Tiktok Shop Ditinjau Dari Aspek Legalitas - Wulandari, Diah Ayu; Feryan Djie, Bryan Storm; Nugroho, Andriyanto Adhi (Media Hukum Indonesia (MHI), 2024)
The existence of an Online Shop/Marketplace is an implementation of the digitalization process in the business sector. This article aims to discover the legality principles related to the acquisition of TikTok Shop and Tokopedia and how Indonesia is prepared to face the era of social commerce. The method used is a literature study that reviews the results of previous research published and supplemented with data from various websites relevant to the topic discussed. The TikTok Shop platform does not yet have clear licensing as an E-Commerce facility in Indonesia. By acquiring Tokopedia, TikTok Shop can operate as an E-Commerce platform. Consumers and business actors must increase their understanding before social commerce can be implemented in Indonesia. It can be concluded that if social commerce such as TikTok Shop is legalized in the future, it is necessary to re-arrange regulations regarding monitoring data use and consumer protection in social commerce so that data used in social media is not misused for buying and selling purposes.